Age-Specific IVF Outcomes in Infertile Women With Baseline FSH Levels ≥20 mIU/mL. (June 2018) - Kushnir, Vitaly A.; Safdie, Maxie; Darmon, Sarah K.; Albertini, David F.; Barad, David H.; Gleicher, Norbert
Introduction: Infertile women with severely diminished ovarian reserve who have low birth chances with in vitro fertilization (IVF) are often denied treatment with autologous oocytes. This study was designed to determine age-specific treatment efficacy and clinical characteristics of infertile women with severely diminished ovarian reserve who had live birth following IVF with autologous oocytes. Methods: This retrospective cohort study investigated 291 infertile women who underwent 482 IVF cycles with autologous oocytes during 2004 to 2016 at our academically affiliated private fertility center. All women were aged <45 years and had maximum baseline follicle-stimulating hormone (FSH) levels ≥20 mIU/mL. Main outcome measures included pregnancy, spontaneous abortion, and live birth rates. Patient and treatment characteristics were compared for women who achieved a live birth to those who did not. Results: Live birth rates were 8.6% per treated woman and 6% per started IVF cycle. The spontaneous abortion risk was 27% per clinical pregnancy. Age-specific live birth rates were highest at 17.2% for women <35 years and lowest at 1.9% for women >42 years. Women who achieved live birth were younger than those who did not (38.0 ± 8.0 vs 40.0 ± 6.0; P = .008), had lower FSH levels (25.0 ± 20.0 vs 32.5 ± 31.0; P = .006), and produced more oocytes (3.0 ± 5.0 vs 1.0 ± 2.0; P < .001), as well as transferrable embryos (2.0 ± 2.0 vs 0.0 ± 1.0; P < .001). Conclusion: Infertile women up to 45 years with severely diminished ovarian reserve achieve better live birth rates than previously reported and should not be denied access to IVF based on elevated FSH levels alone.